Allelopathic, Phytotoxic, and Insecticidal Effects of Thymus proximus Serg. Essential Oil and Its Major Constituents - Zhou, Shixing; Han, Caixia; Zhang, Chenpeng; Kuchkarova, Nigora; Wei, Caixia; Zhang, Chi; Shao, Hua (Frontiers in Plant Science, 2021)
The chemical profile of Thymus proximus essential oil (EO) and its allopathic, phytotoxic and insecticidal activity were evaluated. Carvacrol, p-cymene and γ-terpinene were detected as the major components of the EO, representing 85.9% of the total oil. Fifty g fresh plant material of T. proximus in a 1.5L air tight container completely inhibited seed germination of Amaranthus retroflexus and Poa anuua. Meanwhile, the EO exhibited potent phytotoxic activity, which resulted in 100% germination failure of both test species when 2 mg/mL (for A. retroflexus) and 5 mg/mL (for P. annua) oil was applied. The EO also triggered significant insecticidal activity on Aphis gossypii with a LC50 value of 6.34 ppm. Carvacrol was identified as the main active compound responsible for both the plant suppressing effect and the insecticidal activity of the EO. Our study is the first on the allopathic, phytotoxic and insecticidal activity of T. proximus EO, as well as the determination of the responsible compound, which indicated their potential of being further explored as environment friendly biopesticides.